2008
DOI: 10.1136/ip.2007.017533
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of multifaceted fall-prevention programs for the elderly in residential care

Abstract: 1 online articles that cite this article can be accessed at:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 13 publications
1
24
0
5
Order By: Relevance
“…따라서 허약은 여러 가지 병리적 기전에 의해 발생되고 영향을 미치기 때문에 단일 중재 보다는 다요 인적 중재 프로그램이 지역사회 노인을 대상으로 허약 발생 위험 요인을 감소시키는 효과적인 중재로 수행되고 있다 (Cusimano, Kwok, & Spadafora, 2008). 다요인적 프로그 램은 운동 프로그램, 약물 복용, 기타 중재, 대상자 교육 등의 복합적 적용으로 두 가지 이상 중재 전략을 이용하는 것이다 (Cusimano et al, 2008). 지역사회 허약노인 및 허약 고위 험 노인을 대상으로 다요인적 중재를 실시한 21개의 선행연 구를 분석한 결과 신체적 기능 저하 예방과 허약 위험요인 우 울, 낙상 두려움, 영양결핍 등에 긍정적인 효과가 있는 것으 로 나타났다 (Lightbody, Watkins, Leathley, & Sharma, 2002).…”
unclassified
“…따라서 허약은 여러 가지 병리적 기전에 의해 발생되고 영향을 미치기 때문에 단일 중재 보다는 다요 인적 중재 프로그램이 지역사회 노인을 대상으로 허약 발생 위험 요인을 감소시키는 효과적인 중재로 수행되고 있다 (Cusimano, Kwok, & Spadafora, 2008). 다요인적 프로그 램은 운동 프로그램, 약물 복용, 기타 중재, 대상자 교육 등의 복합적 적용으로 두 가지 이상 중재 전략을 이용하는 것이다 (Cusimano et al, 2008). 지역사회 허약노인 및 허약 고위 험 노인을 대상으로 다요인적 중재를 실시한 21개의 선행연 구를 분석한 결과 신체적 기능 저하 예방과 허약 위험요인 우 울, 낙상 두려움, 영양결핍 등에 긍정적인 효과가 있는 것으 로 나타났다 (Lightbody, Watkins, Leathley, & Sharma, 2002).…”
unclassified
“…28 Studies of multicomponent interventions were done in both reviews. One review 29 showed some efficacy but did not provide a compiled average in risk for all studies used. The other review 28 initially showed no significant reduction in rate of falls or risk of falling, but post hoc analysis did show significance.…”
Section: Retirement Homes and Long-term Carementioning
confidence: 99%
“…Two systematic reviews 28,29 examined studies of interventions to prevent falls among those living in retirement homes or long-term care institutions. Vitamin D supplementation was associated with a reduction in the rate of falls but did not reduce the risk of falling (rate ratio 0.72, 95% CI 0.55-0.95, risk ratio 0.98, 95% CI 0.89-1.09).…”
Section: Retirement Homes and Long-term Carementioning
confidence: 99%
See 1 more Smart Citation
“…Multifaceted interventions can be implemented at the level of the residential care facility6 and at the community level 7. Mostly, exercise interventions for balance and strength are effective in preventing falls8 9 and are often delivered to groups rather than to individuals.…”
mentioning
confidence: 99%